2020
DOI: 10.1002/jmri.27257
|View full text |Cite
|
Sign up to set email alerts
|

Insight Into Myocardial Microstructure of Athletes and Hypertrophic Cardiomyopathy Patients Using Diffusion Tensor Imaging

Abstract: Background: Hypertrophic cardiomyopathy (HCM) remains the commonest cause of sudden cardiac death among young athletes. Differentiating between physiologically adaptive left ventricular (LV) hypertrophy observed in athletes' hearts and pathological HCM remains challenging. By quantifying the diffusion of water molecules, diffusion tensor imaging (DTI) MRI allows voxelwise characterization of myocardial microstructure. Purpose: To explore microstructural differences between healthy volunteers, athletes, and HCM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 22 publications
1
32
2
Order By: Relevance
“…Previous studies have observed absolute E2A to be globally increased in HCM patients compared to controls suggesting that the myocardial sheetlets adopt hypercontracted configurations during systole 13 , 14 , 26 ; however, in this study, we demonstrate this to be the case even in segments with normal thickness and normal perfusion. Previous authors have speculated whether the compressive deformation of intramyocardial blood vessels during systole can explain the increased coronary flow resistance in these patients 27 ; however, results from our study are unable to corroborate this, as absolute E2A did not vary significantly between segments with normal and abnormal perfusion reserve.…”
Section: Discussioncontrasting
confidence: 90%
See 2 more Smart Citations
“…Previous studies have observed absolute E2A to be globally increased in HCM patients compared to controls suggesting that the myocardial sheetlets adopt hypercontracted configurations during systole 13 , 14 , 26 ; however, in this study, we demonstrate this to be the case even in segments with normal thickness and normal perfusion. Previous authors have speculated whether the compressive deformation of intramyocardial blood vessels during systole can explain the increased coronary flow resistance in these patients 27 ; however, results from our study are unable to corroborate this, as absolute E2A did not vary significantly between segments with normal and abnormal perfusion reserve.…”
Section: Discussioncontrasting
confidence: 90%
“…The study sample is relatively small, but in keeping with similar studies. 14 cDTI volunteers were not age-matched to the HCM subjects; however, it is yet to be established whether DTI parameters change with age. The ECV, MPR, and LGE of healthy volunteers were not obtained, as it was not felt ethically justifiable to administer contrast in this cohort.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motion-compensated diffusion encoding overcomes this limitation [160][161][162][163]. Most of the cardiac dMRI studies are based on single diffusion encoding, which has already led to interesting insights in the healthy [28,90,96,161,162] and diseased heart, including myocardial infarction [29], hypertrophic and dilated cardiomyopathy [164], amyloidosis [165] and athlete's heart [166]. Isotropic diffusion encoding can be used to estimate mean diffusivity (MD) in a shorter time compared to conventional single diffusion encoding [71,75].…”
Section: Cardiac Imagingmentioning
confidence: 99%
“…In this issue of JMRI, Das et al reported a cardiac DTI study that compares athletes who developed physiological ventricular hypertrophy with HCM patients and healthy volunteers. 10 DTI data were acquired at mid-systole using a 2 nd -order motion-compensated spin-echo planar imaging sequence. By showing E2A volunteers < E2A athletes < E2A HCM , the study demonstrated that LV hypertrophy may contribute to elevated systolic E2A.…”
mentioning
confidence: 99%